New light-illuminated silk road: emerging silk fibroin-based optical biomedical sensors - Dong, Kaiyi; Zhou, Qian; Gao, Bingbing (Analyst (London), 2024)
Biomedical silk protein optics has become the subject of intensive research aimed at solving the challenges associated with traditional medical devices in terms of biocompatibility and performance balance. With its significant potential for biomedical applications in the field of drug storage and wound monitoring, it is dedicated to reducing the perturbation of neighbouring tissues. The transparency and biocompatibility of silk proteins make them ideal materials in the field of optical device fabrication, effectively overcoming the challenges posed by conventional materials. In this paper, we explore in detail the complex aspects of the design, synthesis and application related to biomedical silk protein optical devices and comprehensively analyse the potential use of silk protein-centric microstructures ( e.g. , micropillars, microneedles, and photonic crystals) in the development of optical devices. This review also offers insights into the challenges of applying silk protein optical devices in healthcare and their future trends, aiming to provide a comprehensive overview of the advances, potential impacts and emerging research directions in the field of biomedical silk protein optical devices. Biomedical silk protein optics has become the subject of intensive research aimed at solving the challenges associated with traditional medical devices in terms of biocompatibility and performance balance.